Betalains and phenolic compounds of leaves and stems of Alternanthera brasiliana and Alternanthera tenella - Deladino, Lorena (2017)
Betacyanins and phenolic compounds from acetonitrile:acidified water extracts of Alternanthera brasiliana and Alternanthera tenella were characterized and quantified using a high-performance liquid chromatography system coupled with diode array and electrospray mass spectrometry detection. Four betacyanins (amaranthine, isoamaranthine, betanin and isobetanin) were tentatively identified and quantified. Twenty eight phenolic compounds of four different families (hydroxybenzoic and hydroxycinnamic acids, flavones and flavonols) were separated and characterized on the basis of their accurate MS and MS/MS information out of which ten compounds were confirmed by authentic standards. These plant species could be considered as an especially rich source of natural bioactive compounds and potential food colorants. A. brasiliana showed the highest betacyanin and polyphenols content (89 μg/g and 35,243 μg/g, respectively). Among polyphenols, flavonols were the more abundant (kaempferol-glucoside, kaempferol-rutinoside and kaempferol-rhamnosyl-rhamnosyl-glycoside). Meanwhile, A. tenella showed a different polyphenols profile with flavones as major compounds (glucopyranosil-vitexin and vitexin). As a novelty, pentosyl-vitexin and pentosyl-isovitexin were detected for the first time in Alternanthera plants. Both A. brasiliana and A. tenella leaves showed high total polyphenol content and in vitro antioxidant activity (FRAP). These results provide an analytical base concerning the phenolic and betalains composition and the antioxidant properties of two members of the promising Alternanthera gender, for subsequent applications, such as functional food ingredients.